About angels - Zamfira Bîrzu (Anastasis: Research in Medieval Culture and Art, 2021)
This work reveals the definition of «angel», a generic classification of angel hierarchies, their main characteristics, a short history about them according to Bible stories and also a history of their representations in iconography. There are also problematised opposite moral aspects, such as: good and bad, spirituality and sin, immortality and ephemerality, sacred and profane, heaven and earth. This theme is analysed from a multiple perspective, such as from a religious, but also from a philosophical and artistic point of view. In the last pages of the article there are 2 paintings entitled «Seraphim» and «Angel» which are visual representations of these heavenly creatures.